Detection of Fraud and Bankruptcy Using The Beneish M-Score and Altman Z-Score Models (Case Study on PT Envy Technologies Indonesia Tbk for the Period 2019–2024) - Deanoviana Galuh Ramadhani; , Mohamad Arief Setiawan; Ahmad Saifi Athoillah (JBS Nexus, 2025)
Financial statements are the primary source of a company financial information which can be the basis for detecting fraud and predicting potential bankruptcy. Financial statement fraud can obscure a company’s true financial condition and it has close relationship with bankruptcy risk, thus it was required comprehensive analysis for identification. This research aims to predict fraud using Beneish M-Score model and to analyze bankruptcy prediction using Altman Z-Score model to the financial statements of PT Envy Technologies Indonesia Tbk in 2019-2024. This research used quantitative approach with applied research objective. The data which was in the form of the company’s financial statements of PT Envy Technologies Indonesia Tbk in 2019-2024. The research results showed that based on M-Score, the company was indicated to do financial statement manipulation in 2019-2020, but there were improvements in 2021-2024. Z-Score value showed that the company was in healthy category in 2019-2020, but it included bankrupt in 2021-2024. These findings indicated that manipulation financial statements could conceal the actual financial condition, so the company appeared healthy. When manipulation was ceased, the poor financial condition to be seen. This research provided valuable insights for management, investors and stakeholders in making strategic decisions and increasing awareness of financial risk.